The impact of L‐citrulline supplementation on glucose homeostasis, lipid profile, and some inflammatory factors in overweight and obese patients with type 2 diabetes: A double‐blind randomized placebo‐controlled trial. (20th April 2021) - Azizi, Samaneh; Mahdavi, Reza; Mobasseri, Majid; Aliasgharzadeh, Soghra; Abbaszadeh, Fatemeh; Ebrahimi‐Mameghani, Mehrangiz
Abstract : This study investigated the impact of L‐citrulline on glucose homeostasis, lipid profile, and inflammatory factors in overweight and obese patients with type 2 diabetes (T2D). In total, 54 participants with T2D were assigned to L‐citrulline (3 g/day L‐citrulline) or placebo groups and tested for 8 weeks. Serum levels of insulin, fasting glucose, hemoglobin A1c (HbA1c), lipid profile, tumor necrosis factor‐α (TNF‐α), high‐sensitivity C‐reactive protein (hs‐CRP), and L‐citrulline were measured pre‐ and post‐intervention. Totally, 45 patients were enrolled in the research. L‐citrulline supplementation decreased serum levels of insulin ( p  = .025), glucose ( p  = .032), HbA1c ( p  = .001), HOMA‐IR ( p  = .037), TNF‐α ( p  = .036), and hs‐CRP ( p  = .027) significantly. At the end of the study, despite the significant decrease in serum levels of triglyceride ( p  = .027) and the increase in high‐density lipoprotein cholesterol levels ( p  < .001) in the L‐citrulline group, no significant differences were found for these parameters between the groups. Moreover, no significant inter‐ and intra‐group changes were observed for dietary intakes, anthropometric indices, total and low‐density lipoprotein cholesterol levels ( p  > .05). In conclusion, L‐citrulline supplementation might improve glucose homeostasis, some lipid factors and inflammatory markers in overweight and obese patients with T2D.